Negative electrode active material for secondary battery and secondary battery using the same

The introduction of a lithium ion conductive phase with dispersed silicon and vanadium particles in a sea island structure addresses the capacity degradation and cycle life issues in silicon-based secondary batteries, enhancing their stability and performance.

JP7664538B2Active Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022511558
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-01-19
Publication Date
2025-04-18
Estimated Expiration
2041-01-19

AI Technical Summary

Technical Problem

Secondary batteries using silicon as a negative electrode active material face a significant decrease in capacity due to the large expansion and contraction of silicon materials during charge and discharge cycles, leading to reduced cycle life.

Method used

A negative electrode active material comprising a lithium ion conductive phase, silicon particles dispersed within the lithium ion conductive phase, and particles containing vanadium dispersed within the lithium ion conductive phase, which forms a sea island structure to limit electrolyte contact and reduce stress from expansion and contraction.

Benefits of technology

The proposed solution significantly improves the cycle life of secondary batteries by suppressing the expansion and contraction of silicon-containing materials, reducing cracking, and enhancing the structural stability of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664538000002
    Figure 0007664538000002
  • Figure 0007664538000003
    Figure 0007664538000003
  • Figure 0007664538000001
    Figure 0007664538000001
Patent Text Reader

Abstract

This negative electrode active material for secondary batteries includes a silicon-containing material. The silicon-containing material includes a lithium ion conductive phase, silicon particles dispersed in the lithium ion conductive phase, and vanadium-containing particles dispersed in the lithium ion conductive phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure mainly relates to a negative electrode active material for a secondary battery.

Background Art

[0002] In recent years, secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for small consumer applications, power storage devices, and electric vehicles because they have a high voltage and a high energy density. Among the demands for increasing the energy density of batteries, the use of a material containing silicon (silicon) that alloys with lithium is expected as a negative electrode active material having a high theoretical capacity density (for example, Patent Document 1).

[0003] However, a material containing silicon has a problem that its capacity tends to decrease when the charge and discharge of the secondary battery are repeated because the expansion and contraction due to charge and discharge are large.

[0004] Therefore, Patent Document 2 discloses a lithium silicate phase represented by Li 2z SiO (2+z) {0 < z < 2}, silicon particles dispersed in the lithium silicate phase, and metal particles mainly composed of one or more metals or alloys selected from Fe, Pb, Zn, Sn, Cu, Ni, and Cr dispersed in the lithium silicate phase, and proposes a negative electrode active material for a non-aqueous electrolyte secondary battery.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Patent Document 2

Summary of the Invention

[0006] According to Patent Document 2, in a nonaqueous electrolyte secondary battery using a silicon material as a negative electrode active material, it is possible to improve the initial charge / discharge efficiency and extend the cycle life. However, the effect of extending the cycle life is not sufficient, and there is room for improvement.

[0007] One aspect of the present disclosure relates to a negative electrode active material for a secondary battery, comprising a silicon-containing material, the silicon-containing material comprising a lithium ion conductive phase, silicon particles dispersed within the lithium ion conductive phase, and particles comprising vanadium dispersed within the lithium ion conductive phase.

[0008] Another aspect of the present disclosure relates to a secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, the negative electrode including the above-mentioned negative electrode active material for secondary batteries.

[0009] By using the negative electrode active material according to the present disclosure, a secondary battery having excellent charge / discharge cycle characteristics can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of a negative electrode active material for a secondary battery (silicon-containing material) according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic perspective view of a secondary battery according to an embodiment of the present disclosure with a portion cut away. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The negative electrode active material for a secondary battery according to an embodiment of the present disclosure includes a silicon-containing material that includes a lithium ion conductive phase, silicon particles dispersed within the lithium ion conductive phase, and particles containing vanadium dispersed within the lithium ion conductive phase.

[0012] Silicon-containing materials have a so-called sea-island structure. Silicon particles (islands) are dispersed in a matrix (sea) of lithium-ion conductive phase and are covered by the lithium-ion conductive phase. In the sea-island structure, contact between the silicon particles and the electrolyte is limited, suppressing side reactions. In addition, stress caused by the expansion and contraction of silicon particles is mitigated by the matrix of the lithium-ion conductive phase.

[0013] Here, particles containing vanadium are dispersed in the lithium ion conductive phase. Vanadium improves the strength of the particles of the silicon-containing material. It is believed that vanadium forms micro-domains of high hardness in the lithium ion conductive phase. By uniformly distributing the micro-domains of high hardness in the matrix of the lithium ion conductive phase, the expansion and contraction of the silicon-containing material due to charging and discharging is suppressed, and the occurrence of cracks in the silicon-containing material and the isolation of a part of the silicon-containing material due to the collapse of particles are suppressed. Thus, the cycle life of the secondary battery is greatly improved.

[0014] In addition, dispersing iron in the lithium ion conductive phase can also suppress the expansion of the silicon-containing material due to charging and discharging, and can also suppress the occurrence of cracks in the particles of the silicon-containing material and the collapse of the particles. In order to achieve such effects, it is necessary to contain a relatively large amount of iron in the lithium ion conductive phase.

[0015] On the other hand, iron tends to react with silicon particles and reduce capacity. Vanadium, when incorporated in the lithium ion conductive phase in a smaller amount than iron, suppresses the expansion and contraction of silicon-containing materials during charging and discharging, and suppresses the occurrence of cracks and the collapse of particles in the silicon-containing material.

[0016] The vanadium content of the silicon-containing material may be, for example, 1000 ppm or less, 500 ppm or less, 300 ppm or less, or 100 ppm or less. From the viewpoint of increasing the effect of increasing the hardness of the lithium ion conductive phase, the vanadium content of the silicon-containing material is preferably 5 ppm or more, may be 10 ppm or more, or may be 30 ppm or more.

[0017] The vanadium content of the silicon-containing material can be measured, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES). Specifically, a sample of the silicon-containing material is completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), the carbon in the solution residue is filtered off, and the resulting filtrate is then analyzed by ICP-AES to measure the vanadium spectrum intensity. Next, a calibration curve is created using a commercially available standard solution of the element, and the vanadium content is calculated.

[0018] In the vanadium-containing particles, vanadium may be contained in at least one selected from the group consisting of vanadium alloys and vanadium carbide. That is, the vanadium-containing particles may be vanadium-containing alloys, vanadium carbide, etc. Among them, vanadium carbide has a Vickers hardness of about 2800, and has the effect of significantly increasing the hardness of the lithium ion conductive phase.

[0019] The vanadium-containing particles may further contain iron. That is, the vanadium-containing particles may be formed of an alloy containing vanadium and iron, or an alloy containing vanadium carbide and iron. The vanadium-iron alloy may contain vanadium and / or vanadium carbide in a dispersed state. Since iron has excellent malleability, cracks and collapses of silicon-containing materials that may occur when charging and discharging are repeated can be significantly suppressed. Thus, the cycle life is significantly improved. In addition, when vanadium and iron are used in combination, such effects specific to iron are fully expressed even if the amount of iron is reduced.

[0020] The iron content in the silicon-containing material may be, for example, 0.01 mass % or more and 10 mass % or less, or 0.1 mass % or more and 3 mass % or less.

[0021] The iron content of silicon-containing materials can be measured by ICP-AES, for example, in the same way as vanadium. Specifically, a sample of silicon-containing material is completely dissolved in a heated acid solution, the carbon in the solution residue is filtered and removed, and then the obtained filtrate is analyzed by ICP-AES to measure the spectral intensity of iron. Next, a calibration curve is created using commercially available standard solutions of the elements, and the iron content is calculated.

[0022] The average particle size of the silicon particles contained in the silicon-containing material may be, for example, 1 nm or more and 1000 nm or less. The average particle size of the silicon particles is preferably 500 nm or less, more preferably 200 nm or less, and even more preferably 50 nm or less. That is, the silicon particles may be fine particles. The smaller the average particle size of the silicon particles, the smaller the volume change during charging and discharging, and the more the structural stability is improved. In addition, the expansion and contraction of the silicon particles are made uniform, and particle cracking is suppressed.

[0023] The average particle size of silicon particles is measured by observing the cross section of the silicon-containing material using a SEM or TEM. Specifically, it is calculated by averaging the maximum diameters of 100 randomly selected silicon particles.

[0024] The lithium ion conductive phase may be at least one selected from the group consisting of a silicon oxide phase, a silicate phase, and a carbon phase, among which the silicate phase has a small irreversible capacity in the early stages of charging and discharging and is suitable for obtaining a high-capacity silicon-containing material.

[0025] The silicon oxide phase contains silicon dioxide as its main component (for example, 95 to 100 mass%). The composition of the composite material containing the silicon oxide phase and silicon particles dispersed therein is, as a whole, SiO x It can be expressed as SiO xIt has a structure in which silicon fine particles are dispersed in amorphous SiO2. The oxygen content ratio x with respect to silicon is, for example, 0.5 ≦ x < 2.0, and 0.8 ≦ x ≦ 1.5 is more preferable.

[0026] The carbon phase can be composed of, for example, low-crystallinity amorphous carbon (i.e., amorphous carbon). The amorphous carbon may be, for example, hard carbon, soft carbon, or the like.

[0027] The silicate phase may contain at least one selected from the group consisting of alkali metal elements and Group II elements. By containing such an element, the irreversible capacity of the silicate phase is more significantly reduced. Among them, a silicate phase containing lithium (hereinafter, also referred to as a lithium silicate phase) is preferable because it has a small irreversible capacity and high initial charge-discharge efficiency. As the alkali metal elements and Group II elements, for example, Li, K, Na, Mg, Ca, Sr, Ba, etc. can be used.

[0028] The silicate phase may further contain an element M other than alkali metal elements and Group II elements. Here, the element M may be, for example, at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, and W.

[0029] The silicate phase preferably contains a lithium silicate represented by the formula: Li 2z SiO 2+z (0 < z < 2). The lithium silicate is lightweight and has excellent lithium ion conductivity. The lithium silicate may be an oxide phase containing Li, Si, and O, and may contain other elements. The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. z preferably satisfies the relationship of 0 < z < 1, and z = 1 / 2 is more preferable.

[0030] When the lithium ion conductive phase is a silicate phase, the content of silicon particles in the silicon-containing material is preferably, for example, 30% by mass or more and 80% by mass or less from the viewpoint of increasing capacity and improving cycle characteristics. By making the content of silicon particles 30% by mass or more, the proportion of the silicate phase is reduced, and the initial charge / discharge efficiency is likely to be improved. By making the content of silicon particles 80% by mass or less, the degree of expansion and contraction of the silicon-containing material during charge / discharge is likely to be reduced. The content of silicon particles in the silicon-containing material is preferably 40% by mass or more, and more preferably 50% by mass or more.

[0031] The composition of the silicate phase can be analyzed by the following method. The composition analysis is preferably performed using the silicon-containing material or the negative electrode composite layer in a discharged state. In addition, from the viewpoint of eliminating the influence of decomposition products of the electrolyte, it is preferable to analyze a sample of the silicon-containing material in the battery before the charge-discharge cycle or at the beginning of the cycle.

[0032] The contents of B, Na, K and Al contained in the silicate layer are determined by quantitative analysis in accordance with, for example, JIS R3105 (1995) (analysis method for borosilicate glass), and the Ca content is determined by quantitative analysis in accordance with JIS R3101 (1995) (analysis method for soda-lime glass).

[0033] The content of each element contained in the silicon-containing material can be measured by ICP-AES, for example, in the same way as vanadium. Specifically, a sample of the silicon-containing material is completely dissolved in a heated acid solution, the carbon in the solution residue is filtered and removed, and then the obtained filtrate is analyzed by ICP-AES to measure the spectral intensity of each element. Next, a calibration curve is created using a commercially available standard solution of each element, and the content of each element is calculated.

[0034] When analyzing the composition of the silicate phase, the silicon-containing material may be taken out of the battery by, for example, the following method. Specifically, the battery is disassembled to take out the negative electrode, and the negative electrode is washed with anhydrous ethyl methyl carbonate or dimethyl carbonate to remove the electrolyte. Next, the negative electrode composite layer is peeled off from the negative electrode current collector and pulverized in a mortar to obtain sample powder. Next, the sample powder is dried in a dry atmosphere for 1 hour and immersed in gently boiling 6M hydrochloric acid for 10 minutes to remove alkali metals such as Na and Li that may be contained in the binder or the like. Next, the sample powder is washed with ion-exchanged water, filtered and dried at 200 °C for 1 hour. Thereafter, by heating in an oxygen atmosphere to remove the carbon component, only the particles of the silicon-containing material can be isolated.

[0035] In the silicon-containing material, a silicate phase, a silicon oxide phase, silicon particles, etc. may exist. By using Si-NMR, these can be distinguished and quantified. The Si content obtained by ICP-AES as described above is the sum of the amount of Si constituting the silicon particles, the amount of Si in the lithium ion conduction phase, and the amount of Si in the silicon oxide phase. On the other hand, the amount of Si constituting the silicon particles and the amount of Si in the silicon oxide phase can be quantified separately using Si-NMR. Therefore, the amount of Si in the silicate phase can be quantified by subtracting the amount of Si constituting the silicon particles and the amount of Si in the silicon oxide phase from the Si content obtained by ICP-AES. For the standard substance required for quantification, a mixture containing a silicate and silicon particles with a known Si content in a predetermined ratio may be used.

[0036] The following shows the desirable Si-NMR measurement conditions.

[0037] <Si-NMR measurement conditions> Measuring device: Solid nuclear magnetic resonance spectrometer (INOVA-400) manufactured by Varian Probe: Varian 7mm CPMAS-2 MAS: 4.2 kHz MAS speed: 4 kHz Pulse: DD (45° pulse + signal acquisition time 1H decoupling) Repeating time: 1200 sec to 3000 sec Observation width: 100 kHz Observation center: around -100 ppm Signal acquisition time: 0.05 sec Number of integrations: 560 Sample amount: 207.6 mg In addition, the quantification of each element in the silicon-containing material can also be performed by SEM-EDX analysis, Auger electron spectroscopy (AES), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc.

[0038] For example, the quantification of each element in the silicon-containing material by SEM-EDX analysis can also be performed by observing the cross-section of the silicon-containing material in the cross-section of the negative electrode composite layer. The cross-section observation can be performed by, for example, the following method. First, disassemble the battery, take out the negative electrode, and obtain the cross-section of the negative electrode composite layer using a cross-section polisher (CP). Observe the cross-section of the negative electrode composite layer using a scanning electron microscope (SEM). Randomly select 10 silicon-containing materials with a maximum particle diameter of 5 μm or more from the cross-sectional image of the backscattered electron image of the negative electrode composite layer, and perform elemental mapping analysis by energy-dispersive X-ray (EDX) for each of them. Calculate the contained area of the target element using image analysis software. The observation magnification is preferably 2000 to 20000 times. Average the measured values of the contained areas of the predetermined elements of the 10 obtained particles.

[0039] Note that a film is formed on the surface of the silicon-containing material due to decomposition of the electrolyte or the like during the charge and discharge process. In addition, the silicon-containing material may be provided with a conductive layer on its surface. Therefore, the mapping analysis by EDX is performed on the region 1 μm or more inside from the peripheral edge of the cross-section of the silicon-containing material so that the film and the conductive layer are not included in the measurement range.

[0040] The following shows the measurement conditions for desirable cross-section SEM-EDX analysis.

[0041] <SEM-EDX measurement conditions> Processing equipment: JEOL, SM-09010 (Cross Section Polisher) Processing conditions: Acceleration voltage 6 kV Current value: 140μA Vacuum degree: 1×10 -3 ~2×10 -3 Pa Measurement equipment: HITACHI SU-70 electron microscope Accelerating voltage during analysis: 10 kV Field: Free mode Probe current mode: Medium Probe Current Range: High Anode Ap.:3 OBJ Ap.:2 Analysis area: 1 μm square Analysis software: EDAX Genesis CPS: 20500 Lsec:50 Time constant: 3.2 The crystallite size of the silicon particles dispersed in the lithium ion conductive phase is preferably 30 nm or less. When the crystallite size of the silicon particles is 30 nm or less, the volume change due to the expansion and contraction of the silicon particles accompanying charging and discharging can be reduced, and the cycle characteristics can be further improved. The crystallite size of the silicon particles is more preferably 2 nm or more and 30 nm or less, and even more preferably 2 nm or more and 20 nm or less. When the crystallite size of the silicon particles is 20 nm or less, the expansion and contraction of the silicon particles can be made uniform, and fine cracks of the particles due to the expansion and contraction of the silicon particles during charging and discharging can be reduced, and the cycle characteristics can be improved.

[0042] The crystallite size of silicon particles is calculated from the half-width of the diffraction peak assigned to the Si(111) plane in the X-ray diffraction (XRD) pattern of the silicon particles by Scherrer's formula.

[0043] At least a part of the surface of the silicon-containing material may be coated with a conductive layer. By forming a conductive layer on the surface of the silicon-containing material, the conductivity of the silicon-containing material can be dramatically increased. The conductive material constituting the conductive layer is preferably a carbon material. The carbon material preferably contains at least one selected from the group consisting of carbon compounds and carbonaceous materials.

[0044] The thickness of the conductive layer is preferably thin enough not to substantially affect the average particle size of the silicon-containing material. In consideration of ensuring electrical conductivity and diffusibility of lithium ions, the thickness of the conductive layer is preferably 1 to 200 nm, more preferably 5 to 100 nm. The thickness of the conductive layer can be measured by observing the cross section of the silicon-containing material using a SEM or a TEM (transmission electron microscope).

[0045] Examples of carbon compounds include compounds containing carbon and hydrogen, and compounds containing carbon, hydrogen, and oxygen. Examples of carbonaceous materials include amorphous carbon with low crystallinity and graphite with high crystallinity. Examples of amorphous carbon include carbon black, coal, coke, charcoal, and activated carbon. Examples of graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles. Among these, amorphous carbon is preferred because it has low hardness and a large buffering effect against silicon particles that change in volume during charging and discharging. The amorphous carbon may be either easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). Examples of carbon black include acetylene black and ketjen black.

[0046] Next, an example of a method for producing a silicon-containing material will be described in detail, in which silicon particles are dispersed in a lithium silicate phase.

[0047] Process (i) The raw material for lithium silicate is a raw material mixture containing a Si raw material and a Li raw material in a predetermined ratio. A vanadium raw material (vanadium carbide, vanadium iron alloy, etc.) is added to the raw material mixture. The raw material mixture may also contain the above-mentioned alkali metal elements, group II elements, and / or element M. The raw material mixture is melted, and the molten liquid is passed through a metal roll to form flakes, thereby producing lithium silicate. The flaked silicate is then crystallized by heat treatment in an air atmosphere at a temperature above the glass transition point and below the melting point. The flaked silicate can also be used without being crystallized. It is also possible to produce silicate by a solid-phase reaction by firing the raw material mixture at a temperature below the melting point without melting it.

[0048] Silicon oxide can be used as the Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as the Li raw material. These may be used alone or in combination of two or more. Raw materials for alkali metal elements, Group II elements, and element M include oxides, hydroxides, carbonates, hydrides, nitrates, sulfates, etc. of each element.

[0049] Process (ii) Next, the lithium silicate is mixed with raw silicon to form a composite. For example, a silicon-containing material, which is a composite particle of lithium silicate and silicon particles (hereinafter also referred to as a silicate composite particle), is produced through the following steps (a) to (c).

[0050] Process (a) Raw silicon powder and lithium silicate powder are mixed in a mass ratio of, for example, 20:80 to 95:5. Coarse silicon particles having an average particle size of several μm to several tens of μm may be used as the raw silicon.

[0051] Process (b) Next, the mixture of raw silicon and lithium silicate is pulverized and compounded while being finely divided using a pulverizing device such as a ball mill. At this time, an organic solvent may be added to the mixture to perform wet pulverization. The organic solvent serves to prevent the material to be pulverized from adhering to the inner wall of the pulverizing container.

[0052] As the organic solvent, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicate esters, metal alkoxides, and the like can be used.

[0053] The raw silicon and lithium silicate may be separately pulverized and then mixed. Alternatively, silicon nanoparticles and amorphous lithium silicate nanoparticles may be produced and mixed without using a pulverizer. The nanoparticles may be produced by a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0054] Process (c) Next, the mixture is heated to 600°C to 1000°C in an inert gas atmosphere (e.g., an atmosphere of argon, nitrogen, etc.), pressurized, and sintered. For sintering, a sintering device capable of applying pressure in an inert atmosphere, such as a hot press, can be used. During sintering, the silicate softens and flows to fill the gaps between the silicon particles. As a result, a dense block-shaped sintered body can be obtained, with the silicate phase as the sea portion and the silicon particles as the island portion. The obtained sintered body can be pulverized to obtain silicate composite particles.

[0055] Process (iii) Subsequently, at least a part of the surface of the composite particle may be coated with a conductive material to form a conductive layer. Examples of a method for coating the surface of the composite particle with a conductive carbon material include a CVD method using a hydrocarbon gas such as acetylene or methane as a raw material, and a method of mixing coal pitch, petroleum pitch, phenol resin, etc. with the composite particle and heating it at 700°C to 950°C in an inert atmosphere (e.g., an atmosphere of argon, nitrogen, etc.) to carbonize it. Carbon black may also be attached to the surface of the composite particle.

[0056] Process (iv) A step of washing the composite particles (including those having a conductive layer on the surface) with an acid may be carried out. For example, by washing the composite particles with an acidic aqueous solution, it is possible to dissolve and remove trace amounts of alkaline components that may be generated when the raw silicon and lithium silicate are combined. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, or carbonic acid, or an aqueous solution of an organic acid such as citric acid or acetic acid can be used.

[0057] FIG. 1 shows a schematic cross section of a silicate composite particle 10 coated with a conductive layer, as an example of a silicon-containing material.

[0058] The silicate composite particle (parent particle) 13 includes a lithium silicate phase 11 and silicon particles 12 dispersed within the lithium silicate phase 11. The silicate composite particle (parent particle) 13 has a sea-island structure in which fine silicon particles 12 are dispersed within the matrix of the lithium silicate phase 11. Particles 15 containing vanadium are also dispersed within the matrix of the lithium silicate phase 11. The vanadium-containing particles 15 usually have an average particle size smaller than that of the silicon particles 12. The surface of the parent particle 13 is covered with a conductive layer 14.

[0059] The average particle size of the vanadium-containing particles 15 is measured by observing a cross section of the silicon-containing material using a SEM or TEM. Specifically, it is determined by averaging the maximum diameters of 100 randomly selected vanadium-containing particles.

[0060] A silicon oxide phase may be dispersed in the lithium silicate phase 11. The SiO2 content in the silicate composite particles (parent particles) 13 measured by Si-NMR is, for example, preferably 30 mass % or less, and more preferably less than 7 mass %.

[0061] The silicate composite particles (base particles) 13 may contain other components in addition to those mentioned above. For example, the base particles 13 may contain less than 10 mass % of reinforcing materials such as carbon materials, oxides such as ZrO2, and carbides.

[0062] Next, the secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode. The negative electrode includes a negative electrode mixture layer including a negative electrode active material including the silicon-containing material. Hereinafter, the negative electrode, positive electrode, electrolyte, and separator included in the secondary battery according to the embodiment of the present disclosure will be described.

[0063] [Negative electrode] The negative electrode comprises, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed by applying a negative electrode slurry, in which the negative electrode mixture is dispersed in a dispersion medium, to the surface of the negative electrode current collector and drying the coating. The coating film after drying may be rolled as necessary.

[0064] The negative electrode mixture contains the above-mentioned silicon-containing material-containing negative electrode active material as an essential component, and may contain optional components such as a binder, a conductive agent, a thickener, etc. The silicon particles of the silicon-containing material can absorb many lithium ions, so that a high-capacity negative electrode can be obtained.

[0065] The negative electrode active material may further include other active material materials that electrochemically absorb and release lithium ions. For example, carbon-based active materials are preferable as other active material materials. Since the volume of the silicon-containing material expands and contracts with charging and discharging, when the ratio of the silicon-containing material in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode current collector is likely to occur with charging and discharging. On the other hand, by using the silicon-containing material and the carbon-based active material in combination, it is possible to achieve excellent cycle characteristics while imparting the high capacity of the silicon particles to the negative electrode. The ratio of the silicon-containing material to the total of the silicon-containing material and the carbon-based active material is, for example, preferably 0.5 to 15 mass%, more preferably 1 to 5 mass%. This makes it easier to achieve both high capacity and improved cycle characteristics.

[0066] Examples of carbon-based active materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferable because it has excellent charge / discharge stability and low irreversible capacity. Graphite means a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. The carbon-based active materials may be used alone or in combination of two or more.

[0067] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc.

[0068] Examples of the binder include fluororesin, polyolefin resin, polyamide resin, polyimide resin, vinyl resin, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and its derivatives, etc. These may be used alone or in combination of two or more.

[0069] Examples of the conductive agent include carbon black, conductive fibers, carbon fluoride, organic conductive materials, etc. These may be used alone or in combination of two or more.

[0070] Examples of the thickener include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These may be used alone or in combination of two or more.

[0071] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and a mixture of these.

[0072] [Positive electrode] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry, in which the positive electrode mixture is dispersed in a dispersion medium, to the surface of the positive electrode current collector and drying the applied film. The dried coating film may be rolled as necessary.

[0073] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, and the like as optional components.

[0074] The positive electrode active material may be a lithium composite metal oxide. For example, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4, Li a Mn 2-b M b O 4、 LiMePO 4、 Li2MePO4F is an example. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≦a≦1.2, 0≦b≦0.9, and 2.0≦c≦2.3. The value a, which indicates the molar ratio of lithium, is a value immediately after the active material is produced, and increases or decreases by charging and discharging.

[0075] The binder and conductive agent may be the same as those exemplified for the negative electrode. As the conductive agent, graphite such as natural graphite or artificial graphite may be used.

[0076] The positive electrode current collector may be a conductive substrate similar to the negative electrode current collector. Examples of the material for the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0077] [Electrolyte] The electrolyte contains a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may contain known additives.

[0078] The solvent used may be an aqueous solvent or a non-aqueous solvent. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, and cyclic carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). The non-aqueous solvents may be used alone or in combination of two or more.

[0079] Examples of lithium salts include lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorine-containing acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorine-containing acid imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc., can be used. One type of lithium salt may be used alone, or two or more types may be used in combination.

[0080] [Separator] It is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, for example, a polyolefin such as polypropylene or polyethylene can be used.

[0081] An example of the structure of the secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and an electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, other types of electrode groups may be applied, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween. The secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.

[0082] FIG. 2 is a schematic perspective view, with a portion cut away, of a prismatic secondary battery according to an embodiment of the present disclosure.

[0083] The battery includes a bottomed rectangular battery case 4, an electrode group 1 and an electrolyte contained in the battery case 4, and a sealing plate 5 that seals the opening of the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them. The sealing plate 5 includes a liquid injection hole blocked by a plug 8, and a negative electrode terminal 6 insulated from the sealing plate 5 by a gasket 7.

[0084] One end of a negative electrode lead 3 is attached to the negative electrode current collector by welding or the like. One end of a positive electrode lead 2 is attached to the positive electrode current collector by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to a sealing plate 5.

[0085] The present disclosure will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0086] <Example 1> [Synthesis of lithium silicate] Lithium carbonate and silicon dioxide were mixed in a molar ratio of Li2CO3:SiO2 = 34:66, the mixture was melted in an inert gas atmosphere at 1500℃ for 5 hours, the molten liquid was passed through a metal roller to form flakes, and then heat-treated at 750℃ for 5 hours to obtain lithium silicate (Li2Si2O5). The lithium silicate was pulverized to an average particle size of 10μm.

[0087] [Preparation of silicon-containing materials] In an inert atmosphere, Si powder (3N, average particle size 10 μm) and Li2Si2O5 powder (average particle size 10 μm) were mixed in a mass ratio of 58:42, and a predetermined amount of vanadium-iron alloy particles containing vanadium simple substance and vanadium carbide in a dispersed state were added, and the mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5). 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was ground at 200 rpm for 50 hours. The powder was then removed in an inert atmosphere and heat-treated at 800 °C for 4 hours in an inert atmosphere to obtain silicate composite particles containing 30 ppm vanadium and 1.3 mass % iron as silicon-containing material A1.

[0088] The silicon-containing material A1 was pulverized and passed through a 40 μm mesh, then mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation) and heat-treated at 800° C. in an inert atmosphere to coat the surface of the silicon-containing material A1 with carbon to form a conductive layer. The amount of carbon coating was about 5 mass% based on the total of the silicon-containing material A1 and the conductive layer. Then, using a sieve, silicon-containing material A1 with an average particle size of 5 μm and a conductive layer was obtained.

[0089] [Analysis of silicon-containing materials] TEM observation of the cross section of the silicon-containing material A1 showed that the average particle size of the silicon particles was less than 50 nm. SEM observation of the cross section of the silicon-containing material A1 showed that the powder containing the silicon particles and vanadium carbide was dispersed almost uniformly in the silicate phase.

[0090] In the XRD pattern of the silicon-containing material A1, peaks due to Si and Li2Si2O5 were confirmed. No SiO2 peak was observed at 2θ=25°.

[0091] As a result of measuring the silicon-containing material A1 by Si-NMR, the SiO2 content was found to be below the lower detection limit.

[0092] The vanadium and iron contents were determined by ICP-AES.

[0093] [Preparation of negative electrode] A mixture containing a silicon-containing material A1 having a conductive layer and graphite in a mass ratio of 5:95, sodium salt of carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 97.5:1.0:1.5, water was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix) to prepare a negative electrode slurry. Next, the negative electrode slurry was applied to both sides of a copper foil, the coating was dried, and then the mixture was rolled to give a negative electrode slurry having a density of 1.6 g / cm on both sides of the copper foil. 3 Thus, a negative electrode A2 having the above negative electrode mixture layer formed thereon was obtained.

[0094] [Preparation of positive electrode] Lithium cobalt oxide, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. The positive electrode slurry was then applied to both sides of an aluminum foil, the coating was dried, and the mixture was rolled to give a positive electrode slurry having a density of 3.6 g / cm on both sides of the aluminum foil. 3 Thus, a positive electrode having a positive electrode mixture layer of this formula was obtained.

[0095] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7.

[0096] [Preparation of secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator interposed therebetween so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was poured in and the opening of the exterior body was sealed to obtain a secondary battery A1.

[0097] <Comparative Example 1> A negative electrode R1 and a secondary battery R1 were obtained in the same manner as in Example 1, except that iron was added to the mixture of Si powder and Li2Si2O5 powder instead of vanadium carbide to synthesize silicate composite particles (silicon-containing material R1) containing 1.7 mass % iron.

[0098] [evaluation] (Cycle life) For each of the batteries of Example 1 and Comparative Example 1, charging and discharging were repeated under the following conditions to evaluate the cycle life.

[0099] <Charging> At 25° C., constant current charging was performed at a current of 1 It (800 mA) until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 It (40 mA).

[0100] <Discharge> At 25° C., constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V.

[0101] The rest period between charging and discharging was 10 minutes. The number of cycles required to reach 80% of the discharge capacity in the first cycle was measured and taken as the cycle life. The results are shown in Table 1.

[0102] [Table 1]

[0103] From Table 1, it can be seen that by dispersing particles containing vanadium in the lithium ion conductive phase, the cycle life is significantly improved compared to the case where iron is dispersed in the lithium ion conductive phase. [Industrial Applicability]

[0104] The secondary battery negative electrode according to the present disclosure is useful in secondary batteries that serve as the main power sources for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]

[0105] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 10. Silicate composite particles having a conductive layer 11 Lithium silicate phase 12 Silicon particles 13 Silicate composite particles (base particles) 14 Conductive layer 15 Particles containing vanadium

Claims

1. a silicon-containing material; the silicon-containing material comprises a lithium ion conducting phase, silicon particles dispersed within the lithium ion conducting phase, and particles comprising vanadium dispersed within the lithium ion conducting phase; The vanadium-containing particles include at least one selected from the group consisting of vanadium alloys and vanadium carbide.

2. 2 . The negative electrode active material for a secondary battery according to claim 1 , wherein the content of said vanadium contained in said silicon-containing material is 1000 ppm or less.

3. The negative electrode active material for a secondary battery according to claim 1 , wherein the vanadium-containing particles contain iron.

4. 4. The negative electrode active material for a secondary battery according to claim 3, wherein the content of the iron contained in the silicon-containing material is 0.01% by mass or more and 10% by mass or less.

5. 5. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon particles have an average particle size of 1 nm or more and 1000 nm or less.

6. 6. The negative electrode active material for a secondary battery according to claim 1, wherein the lithium ion conductive phase is at least one selected from the group consisting of a silicon oxide phase, a silicate phase, and a carbon phase.

7. the lithium ion conducting phase comprises the silicate phase, 7. The negative electrode active material for a secondary battery according to claim 6, wherein the silicate phase contains at least one selected from the group consisting of alkali metal elements and Group II elements.

8. The silicate phase further comprises an element M, 8. The negative electrode active material for a secondary battery according to claim 7, wherein the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

9. The silicate phase has the formula: Li 2z SiO 2+z 9. The negative electrode active material for a secondary battery according to claim 6, comprising a lithium silicate represented by (0<z<2).

10. A battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode; A secondary battery, wherein the negative electrode comprises the negative electrode active material for secondary batteries according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of modified lithium iron silicate positive electrode material

    CN107863503A

  • Cathode active material for lithium ion battery and method for producing the same

    JP2013086979A

  • Phosphate compound, positive electrode material for secondary battery, and method for producing secondary battery

    JP2014056722A

  • Secondary battery positive electrode active material and method for producing the same

    JP2014120324A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    WO2016035290A1